Sub-Acute Toxicity of Alkaloids Extract from Drimia maritima in Pregnant & Non-Pregnant Females of Wistar Rats - FADLI , Hazar; DEROUICHE , Fatiha; DJABOU , Chaima; BOUZIDI , Abdelouahab Supervisor (Setif 1 University Ferhat Abbas . Faculty of Natural and Life Sciences, 2025)
Drimia maritima, commonly known as sea squill, is a bulbous plant native to the Mediterranean basin, including Algeria. It has been used for centuries in traditional medicine for its cardiotonic, diuretic, and anti-inflammatory properties. Despite its therapeutic uses for conditions like asthma and jaundice, the plant is also known for its high toxicity, mainly due to potent compounds such as bufadienolides. Its toxicity is so notable that it has historically been used as a rodenticide. The primary aim of this study was to perform a phytochemical analysis of the alkaloids present in Drimia maritima bulbs and to carry out a comprehensive toxicity assessment. Specifically, the study sought to evaluate its effects on biochemical and hematological markers and embryonic development in female Wistar rats. Bulbs of Drimia maritima were collected from the Sétif region in northeastern Algeria. Total alkaloids were extracted from fresh plant material using a liquid-liquid extraction method, with a yield of approximately 0.036% from the raw plant material. The presence of alkaloids was confirmed in the final extract using thin-layer chromatography (TLC) with Dragendorff’s reagent as a detection agent. For toxicity evaluation, healthy adult female Wistar rats were used. A sub-acute toxicity study was conducted, where the treated group received a daily oral dose of 5.1761 mg/kg for five days. This dose corresponds to 1/100 of the reported LD₅₀. Assessments included body and organ weight monitoring, complete hematological and biochemical analysis (to evaluate liver and kidney function), and reproductive hormone measurements. To assess embryotoxicity, pregnant females were treated during gestation. On gestation day 20 (GD20), they were sacrificed, and the number and weight of fetuses were carefully examined. No mortality was observed during the sub-acute test. However, transient mild clinical signs such as tachycardia and slight convulsions were recorded shortly after administration. In non-pregnant rats, significant body weight loss was observed in the treated group. While no gross anatomical changes in organs were noted, a statistically significant increase in the relative spleen weight was recorded. Biochemical analysis revealed a notable and significant decrease in serum urea and creatinine levels (renal markers) and in liver enzymes AST and ALT. Hematological evaluation showed a significant reduction in platelet count (PLT) and plateletcrit (PCT). In pregnant rats, maternal body weight remained stable throughout gestation. However, the extract showed strong signs of developmental toxicity. The average pup weight in the treated group was reduced by approximately 81.93%, indicating severe intrauterine growth restriction. The number of pups also decreased, although this change was not statistically significant. Hormonal analysis revealed a significant increase in progesterone levels in treated females. These findings confirm that the alkaloid extract of Drimia maritima, even at a low sub-acute dose, induces moderate and potentially reversible toxicity. It clearly affects organ function and reproductive outcomes. The sharp decline in pup weight points to a major embryotoxic risk, likely due to placental transfer of toxic compounds. The atypical decrease in liver and kidney markers is unusual for a toxic substance and warrants further investigation into the specific mechanism of action of this extract. While this research provides crucial preliminary data, the specific alkaloids responsible for these effects remain unidentified. Future work should focus on isolating and structurally characterizing these active compounds and exploring their mechanisms to better understand the balance between the plant’s therapeutic potential and its toxicological risks.
تُعّد نبتة بصل العنصل (maritima Drimia (من النباتات البصلية التي يعود أصلها إلى حوض البحر األبيض المتوسط، بما أساسياً في الطب التقليدي، حيث استُخدمت لخصائصها القلبية المدعمة، والمدّرة في ذلك الجزائر. لطالما كانت هذه النبتة مكوناً للبول، والمضادة لاللتهابات. وعلى الرغم من استعمالها لعالج حاالت مثل الربو واليرقان، إال أنها تُعرف بس ّميتها العالية، التي تُعزى إلى احتوائها على مركبات قوية وفعالة، أبرزها البوفادينوليدات، الهدف من هذه الدراسة هو إجراء تحليل كيميائي نباتي لمستخلص القلويدات الموجود في وتقييم سُميته بشكل شامل. وقد ر ّكزت الدراسة بشكل خاص على تأثير المستخلص على المؤشرات البيوكيميائية والدموية، باإلضافة إلى دراسة تأثيره على تطور األجنة لدى إناث فئران ويستار. تم جمع البصالت من منطقة سطيف الواقعة شمال شرق الجزائر. وتم استخراج القلويدات الكلية من المادة النباتية الطازجة عبر ُ تقنية االستخالص السائل-السائل، ما أسفر عن مردود يُقّدر بحوالي 0.036 ّكد وجود القلويدات في % من المادة الخام. وأ المستخلص النهائي من خالل تحليل نوعي باستخدام كروماتوغرافيا الطبقة الرقيقة (TLC(، مع كاشف دراغندورف كمادة كاشفة. شملت الدراسة استعمال إناث فئران ويستار بالغة وسليمة إلجراء اختبار السمية شبه الحادة، حيث تلقّت مجموعة المعالجة جرعة ّ فموية يومية قدرها 5.1761 ملغ/كغ لمدة خمسة أيام، وهي تعادل 100/1 من الجرعة المميتة المتوسطة (50LD(، غ المبل عنها. وشمل التقييم مراقبة تطور الوزن الجسماني ووزن األعضاء، باإلضافة إلى إجراء تحاليل دموية وكيميائية حيوية لتقييم وظائف الكبد والكلى، وتحليل مستويات الهرمونات التناسلية. لم تُس َّجل أي وفيات خالل اختبار السمية، لكن ظهرت عالمات سريرية خفيفة وعابرة، مثل تسارع في ضربات القلب وتشنجات طفيفة بعد الجرعة. فيما يخص الفئران غير الحوامل، لوحظ انخفاض كبير في الوزن الجسماني في نهاية التجربة، مقارن ًة بالمجموعة الضابطة. لم تُس َّجل تغّيرات ظاهرية في األعضاء، إال أنه لوحظ ارتفاع معنوي في الوزن النسبي للطحال. كشفت التحاليل البيوكيميائية عن انخفاض معنوي ومفاجئ في مستويات اليوريا والكرياتينين، إلى جانب انخفاض في إنزيمات الكبد AST و ALT ، أما التحاليل الدموية، فأظهرت انخفا ًضا معنويًا في عدد الصفائح الدموية (PLT (ومؤشر كريات الصفيحات )PCT )والهيموغلوبين )HGB) بالنسبة للفئران الحوامل، لم يُس َّجل تغيّر في وزن األمهات خالل فترة الحمل، إال أن المستخلص أظهر مؤشرات واضحة على وجود سمية نمائية. إذ سُ ِّّجل انخفاض كبير ج ًدا بنسبة تُقَّدر بحوالي 81.93% في متوسط وزن األجنة في مجموعة المعالجة بالمجموعة الضابطة، مما يدل على تقييد شديد للنمو داخل الرحم،. كما لوحظ انخفاض في عدد األجنة، غير أن هذا مقارنةً التغيير لم يكن معنويًا. أما التحاليل الهرمونية، فقد أظهرت ارتفا ًعا معنويًا في مستوى هرمون البروجسترون لدى اإلناث المعال (maritima Drimia (، حتى بجرعة منخفضة ولفترة قصيرة، َجة، تُشير نتائج هذه الدراسة إلى أن مستخلص قلويدات يُمكن أن يُسبب سمية معتدلة قابلة للعكس، مع تأثير واضح على وظائف األعضاء والتكاثر. يُبرز االنخفاض الحاد في وزن األجنة خطورة هذا المستخلص على تطور األجنة، ما يُعّزز فرضية عبور المركبات السامة للمشيمة. كما أن االنخفاض غير المتوقع في مؤشرات الكبد والكلى يستدعي مزيدًا من البحث لفهم آلية تأثير هذه القلويدات.. ورغم أهمية النتائج التي توصلنا إليها، ال تزال المركبات الفعالة المسؤولة عن هذه التأثيرات غير معروفة. من الضروري مستقبالً عزل هذه القلويدات وتحديد تركيبها البنيوي، إلى جانب دراسة آليات تأثيرها بدقة، لتحقيق فهم أعمق للتوازن بين اإلمكانات العالجية لهذا النبات والمخاطر السمية المرتبطة به
Keywords: Drimia maritima; alkaloid extract